Very Late Relapse of Acute Promyelocytic Leukemia 17 Years after Continuous Remission - Sakurai, Masatoshi (Intern Med, 2018)
The prognosis of acute promyelocytic leukemia (APL) has been improved by the combination of all-trans retinoic acid (ATRA) with chemotherapy. Nonetheless, relapse occurs in a certain proportion of patients, mostly within three to four years after treatment. We herein report a patient treated with ATRA and chemotherapy achieving remission who relapsed approximately 17 years after the treatment. A literature review identified 5 additional reported cases of APL relapse after more than 10 years. None of them presented with generally established risk factors for relapse, such as a high leukocyte count. The potential for late relapse of APL occurring more than 10 years after treatment should be recognized.